Determinants of South American bank credit: An approach to panel data - Vitor Gomes Reginato; Marina Silva da Cuhna; Marcos Roberto Vasconcelos (Estudios Económicos, 2020)
The objective of this paper is to analyze the determinants of the domestic banking credit in the South American countries, based on panel data, for the period 2000 to 2016. The results indicate that domestic deposits and liabilities to non-residents contribute positively to the growth of private credit, with domestic funding having a more representative impact than foreign funding. Economic growth leads to a greater demand for credit and an increase in credit, while higher domestic and US interest rates reduce credit growth. Rising inflation also negatively affect private sector credit. In addition, as regards credit composition, domestic deposits and economic growth are the main components of credit expansion, and, in turn, inflation and domestic interest rates contribute negatively.